Design, synthesis and molecular docking studies of 5,6-difluoro-1H-benzo[d]imidazole derivatives as effective binders to GABAA receptor with potent anticonvulsant activity - Raghu, M.S.; Swarup, H.A.; Prathibha, B.S.; Yogesh Kumar, K.; Pradeep Kumar, C.B.; Alharti, Fahad A.; Prashanth, M.K.; Jeon, Byong-Hun (Journal of molecular structure, 2023)
•A series of new 5,6-difluoro-1H-benzo[d]imidazole derivatives were designed and synthesized.•The compounds 4d and 4e exhibited specific anticonvulsant activity in MES and scPTZ models.•All the compounds showed more PI values than that of carbamazepine.•Compound 4d and 4e exhibits potent binding affinity on GABAA receptor.•The experimental results were supported by the molecular docking studies. In the search for more effective and safer antiepileptic drugs, a series of 5,6-difluoro-1H-benzo[d]imidazole derivatives (4a-e) were designed and synthesized. Elemental analysis, 1H NMR, 13C NMR and mass spectroscopic techniques were used to confirm the structure and purity of the resultant compounds. Maximum electroshock (MES) and subcutaneous pentylenetetrazole (scPTZ) screenings were used in mice for preliminary anticonvulsant screening. In each of the animals used for anticonvulsant assessment, two compounds, 4d and 4e, demonstrated positive anticonvulsant activity with 100% protection. The most active congeners, compounds 4d and 4e, were quantified to be 2.68 and 3.26 folds, respectively, more potent than the reference medication, carbamazepine, in the MES model. The rotarod technique was used to test all the substances for acute neurotoxicity to detect motor impairment, and all the substances passed the test. Additionally, the in vitro binding studies revealed that compounds 4d and 4e had the most affinity for binding to the GABAA receptor, with IC50 values of 0.74 and 0.18 μM, respectively. Additionally, the GABA concentration in rat brains was examined. The findings indicated that both compounds 4d and 4e may have influenced the GABA system by raising GABA concentration in rat brains. The GABAA receptor and drug binding modes were examined using molecular docking. Compounds 4d and 4e demonstrated substantial interactions with residues at the GABAA receptor's benzodiazepine binding site. According to Lipinski's rule of five, all the compounds show promise as potential oral medication candidates. Thus, the current study has offered suitable epilepsy research subjects for further study. [Display omitted]